Venezuelan Migration in Argentina and Collective Action Strategies (2015-2022) (Colección, 2023)
This work aims to advance in a mapping of Venezuelan migrant organizations in Argentina and analyze their collective action strategy between 2015 and the present. Through a quantitative-qualitative study, 52 organizations are identified, most of them located in the City of Buenos Aires. Among them, two profiles predominate: those that provide support and social assistance and those that add professionals. In terms of resources and strategies, Venezuelan collective action is characterized by great pragmatism and the ability to adapt to changes in the national and regional context. The work identifies two stages in its evolution.
Keywords: Venezuelan Migration; Collective Action; Argentina; Organizations